Crystal structure of ((4-(4-bromophenyl)-1H-pyrrol-3-yl)methyl)ferrocene, C21H16BrFeNO - Tang Wenqiang; Gao Yanrong; Xu Xiaona; Zhu Zhoujing (Zeitschrift für Kristallographie - New Crystal Structures)
C21H16BrFeNO, monoclinic, P21/c (no. 14), a = 14.6736(9) Å, b = 9.5595(6) Å, c = 12.7860(7) Å, β = 105.579(2)°, V = 1727.63(18) Å3, Z = 4, Rgt(F) = 0.0452 wRref(F2) = 0.0919, T = 170 K.